Dissemination, Adoption and Adaptation of Project Innovations in Higher Education. - McKenzie, Jo; Alexander, Shirley; Harper, Carly; Anderson, Susan (Carrick Institute for Learning and Teaching in Higher Education, 2005)
Final report on this project which aimed to improve understanding of the interacting systems of conditions which favour the dissemination, adoption, adaptation and implementation of innovations aimed at improving teaching and learning in higher education. The researchers sought to identify and analyse successful cases of ideas, projects and processes ('innovations'). A successful case was defined as one in which the innovation had been disseminated and successfully adopted, adapted, implemented and sustained in contexts beyond the development context. Particular attention was given to cases where there was clear evidence of improvement in teaching and learning or features which were likely to afford improvement. The project took a two-phase approach. Phase 1 involved investigation of funding agency and other contexts associated with project development and adoption, along with the identification of cases of successful innovations. Phase 2 explored the successful case studies in more detail, focusing on the interacting system of features and conditions which contributed to the innovations' success in being disseminated, adapted, implemented and sustained in a new context.